DIGITAL TRANSFORMATION IN THE JUSTICE SYSTEM: ENHANCING EFFICIENCY AND ACCESSIBILITY OF LEGAL SERVICES - Latif, Muhamad; Innash, Ar-Rahiim (JIL : Journal of Indonesian Law, 2024)
This research aims to examine digital transformation in the field of law and its implications for the justice system in Indonesia. The method used literature review by analyzing variety of relevant literature, including books, articles, journals, and previous research that related to digital transformation in law. Data is analyzed qualitatively by examining the development of digital technology, its impact on legal practices, and the challenges faced. The research results show that digital transformation in law refers to the utilization of information and communication technology, such as e-court, e-filing, and cloud-based data management, aimed at increasing efficiency, transparency, and expanding access to justice. However, several challenges such as data protection, technology access, the digital divide, and regulatory changes still need further attention. Therefore, collaboration between the government, legal institutions, and technology plays a crucial role in realizing a more transparent, efficient, and just justice system.